Synthesis and Characterization of Mesoporous NaX Zeolite from Kaolin Loading of Soursop Leaves Extract (Annona muricata Linn.) - Nasifah, Ilmin; Khalifah, Susi Nurul; Hayati, Elok Kamilah (ALCHEMY, 2017)
Mesoporous NaX zeolite has been synthesized from calcined kaolin with the addition of 5M NaOH and CTABr surfactant as mesoporous template by hydrothermal method. The result of synthesis was used as anticancer loading agent of ethanol extract soursop leaves. Characteristics of zeolite were studied by XRD, IR spestroscopy, Nitrogen Adsorption and SEManalysis. The mesoporous NaX zeolite has been formed with mixing of A, Y, kaolinite and quartz phases. The surface of zeolite particles has changed from amorphous to regular and uniform particles. The pores of NaX zeolite belongs to mesoporous type with size 6.13 nm. Loading process of soursop leaves extract on zeolite decreased intensity and crystallinity of zeolite peaks. The new absorption in soursop leaves extract loaded on zeolite spectra was detected at 2928.174 cm-1. The surface of zeolite seen to be compact and irregular.